Questions and Considerations on Anesthesia in the Elderly - Evangelina Dávila Cabo de Villa (Medisur)
Scientific advances have enhanced progresses in the understanding of diseases’ pathophysiology, thus enabling the performance of a higher number of surgical procedures. These procedures, also superior in complexity and quality, are supported by anesthesia methods. The accurate use of drugs, the concern for providing more benefits for the sick as well as technological updating are key objectives in anesthesiology, especially in the elderly. These patients require individualization in the performance of therapeutic strategies. Therefore, the present pamphlet, structured in questions, is an invitation to mental exercising and reflection aimed at contributing to the fulfillment of ideas in order to support attendance maximization in the elderly.